Návrh modernizace železniční stanice Polička - Zvejška, Ivo (Vysoké učení technické v Brně. Fakulta stavební, 2014)
Cílem diplomové práce je návrh rekonstrukce železniční stanice Polička, tak aby splňovala podmínky pro pohyb osob se sníženou schopností pohybu a orientace. V té souvislosti bylo nutno navrhnout nástupiště s výškou nástupní hrany 550 mm nad temenem kolejnice. Dále byla zvýšena rychlost v hlavní koleji a zrušeno napojení zrušených vleček. Rovněž byla navržena rekonstrukce odvodnění.

The goal of the diploma thesis is a design of the reconstruction of the Polička railway station in aim to fulfil the requirements for the movement of people with reduced mobility. It was necessary to design platforms with a height of the platform edge 550 mm above rail level. It was also required to increase the design speed in main tracks as well as to reconstruct conections of sidings. There was also included the design of reconstruction of drainage system of railway tracks.
Design of Modernization of Polička Railway Station
Keywords: Železniční stanice; rekonstrukce; odvodnění; nástupiště; výhybky; geometrické parametry koleje; Railway station; reconstruction; drainage; platforms; switches; track alignment